Effect of Linear Polyacrylamide on the Properties of semi–IPN Hydrogels Based on N, N’–Dimethylacrylamide, and Maleic Acid - Bui, Thi Cam Phan; Huynh, Nguyen Anh Tuan (Journal of Technical Education Science, 2023)
In this work, the semi–interpenetrating polymer network hydrogels based on Polyacrylamide; N, N’–Dimethylacrylamide, and Maleic acid were synthesized and investigated by changing the content of linear polyacrylamide in the obtained materials. The chemical properties, morphology, swelling behaviors in distilled water, and mechanical properties of the hydrogels were investigated. Fourier transform infrared spectra confirmed the polymerization ability of monomers, scanning electronic microscopy images showed that the pore size could be controlled by the added volume of linear polyacrylamide was in the range of 252.8 ± 5.0 888.5 ± 3.5 µm. The swelling ratio and the mechanical properties of the hydrogels increased with increasing linear polyacrylamide content. All of the results in this work showed that semi–interpenetrating polymer network hydrogels based on Polyacrylamide; N, N’–Dimethylacrylamide, and Maleic acid had a high swelling ratio, good water retention, thermal properties, and mechanical properties. Potential applications of the obtained hydrogels are in progress.